Angiotensin II upregulates type-1 angiotensin II receptors in renal proximal tubule. - Cheng, H F (1995)
Angiotensin II (Ang II) is an important regulator of proximal tubule salt and water reabsorption. Recent studies indicate that rabbit proximal tubule angiotensin II receptors are the type-1 (AT1R) subtype. We studied the effect of Ang II on proximal tubule receptor expression. Rabbits were treated with either angiotensin converting enzyme inhibitors or a low salt diet to modulate endogenous Ang II levels. In captopril-treated rabbits, liver and glomerular AT1R mRNA levels increased 242 +/- 125 and 141 +/- 60%, respectively (n = 6-7; P < 0.05), as determined by quantitative PCR. In contrast, proximal tubule AT1R mRNA levels decreased 40 +/- 11% (n = 6; P < 0.05). Binding of 125I Ang II to renal cortical basolateral membranes of captopril-treated rabbits decreased from 2.9 +/- 0.55 to 1.4 +/- 0.17 fmol/mg protein (n = 6; P < 0.025). In rabbits fed a sodium chloride-deficient diet for 4 wk, AT1R mRNA levels decreased 52 +/- 11% in liver and 43 +/- 7% in glomeruli (n = 4-5; P < 0.05), whereas they increased 141 +/- 85% (n = 5; P < 0.05) in proximal tubule. In basolateral membranes from rabbits on the sodium chloride-deficient diet, specific binding of 125I Ang II increased from 2.1 +/- 0.2 to 4.3 +/- 1.1 fmol/mg protein (n = 7; P < 0.05). To determine whether Ang II directly regulates expression of proximal tubule AT1 receptors, further studies were performed in cultured proximal tubule cells grown from microdissected S1 segments of rabbit proximal tubules and immortalized by transfection with a replication-defective SV40 vector. Incubation of these cells with Ang II (10(-11) to 10(-7) M) led to concentration-dependent increases in both AT1R mRNA levels and specific 125I Ang II binding. Pretreatment with pertussis toxin inhibited Ang II stimulation of AT1R mRNA. AT1R mRNA expression was decreased by either forskolin or a nonhydrolyzable cAMP analogue (dibutryl cAMP). Simultaneous Ang II administration overcame the inhibitory effect of forskolin but not dibutryl cAMP. These results indicate that proximal tubule AT1R expression is regulated by ambient Ang II levels, and Ang II increases AT1R mRNA at least in part by decreasing proximal tubule cAMP generation through a pertussis toxin-sensitive mechanism. Upregulation of proximal tubule AT1R by Ang II may be important in mediating enhanced proximal tubule sodium reabsorption in states of elevated systemic or intrarenal Ang II.